2023
DOI: 10.3390/ma16206799
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Spectroscopic, Thermal, and Mechanical Characterization of Biocomposites of Poly(butylene succinate) and Onion Peels or Durum Wheat Bran

Emil Sasimowski,
Marta Grochowicz,
Łukasz Szajnecki

Abstract: The utilization of plant based fillers: onion peels (OP) and durum wheat bran (WB) to obtain sustainable biocomposite materials with poly(butylene succinate) (PBS) is presented in this paper. The biocomposites were first obtained in pellet form by extrusion method and then injection moldings were made from the pellets. Two kinds of biocomposites were fabricated containing 15% and 30% wt. of OP or WB. Additionally, pure PBS moldings were prepared for comparative purposes. The effect of the filler type and its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…This is a relatively new process, but research indicates it could be a lucrative one with the generation of value-added biobased food and feed ingredients [20,21]. Studies have also shown that waste material, such as the shells of nuts [22] or onion peels [23], can be used in the production of bio composite films with improved mechanical properties. Numerous studies have been conducted focusing on the extraction of bioactive compounds from fruit and vegetable waste streams, mostly on a small scale but with clearly demonstrated applications in both the food industry and cosmetic industry [19,[24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…This is a relatively new process, but research indicates it could be a lucrative one with the generation of value-added biobased food and feed ingredients [20,21]. Studies have also shown that waste material, such as the shells of nuts [22] or onion peels [23], can be used in the production of bio composite films with improved mechanical properties. Numerous studies have been conducted focusing on the extraction of bioactive compounds from fruit and vegetable waste streams, mostly on a small scale but with clearly demonstrated applications in both the food industry and cosmetic industry [19,[24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%